The multicolored Asian lady beetle, Harmonia axyridis: A review of its biology, uses in biological control, and non-target impacts - Koch, R L (University of Arizona Library, 2003)
Throughout the last century, the multicolored Asian lady beetle, Harmonia axyridis (Pallas) has been studied quite extensively, with topics ranging from genetics and evolution to population dynamics and applied biological control being covered. Much of the early work on H. axyridis was conducted in the native Asian range. From the 1980's to the present, numerous European and North American studies have added to the body of literature on H. axyridis. H. axyridis has recently gained attention in North America both as a biological control agent and as a pest. This literature review was compiled for two reasons. First, to assist other researchers as a reference, summarizing most of the voluminous body of literature on H. axyridis pertaining to its biology, life history, uses in biological control, and potential non-target impacts. Secondly, to be a case study on the impacts of an exotic generalist predator.